2015
DOI: 10.1177/0095327x15607810
|View full text |Cite
|
Sign up to set email alerts
|

Employment Gaps Between Military Spouses and Matched Civilians

Abstract: Drawing upon data from the Deployment Life Study, this article examines whether female military spouses (SPs) are disadvantaged relative to matched civilian peers in terms of hours worked and earnings, paying particular attention to gaps among the highest educated women. Female SPs do earn less than comparable civilian peers in terms of raw dollars and percentage earnings. Moreover, military wives who are part of the labor force work as many hours as their civilian counterparts, but still earn significantly le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…There are a number of theories of family resilience in the literature, but most build on Hill's original model (see Meadows et al, 2015, for a review of some of these models), and all recognize that there are individual or family-level differences in the degree to which a given stressor affects different families. These models all have a number of common themes.…”
Section: Family Resilience Models and Theorymentioning
confidence: 99%
“…There are a number of theories of family resilience in the literature, but most build on Hill's original model (see Meadows et al, 2015, for a review of some of these models), and all recognize that there are individual or family-level differences in the degree to which a given stressor affects different families. These models all have a number of common themes.…”
Section: Family Resilience Models and Theorymentioning
confidence: 99%
“…A body of existing research demonstrates the existence of differences in employment outcomes between military and civilian spouses. In particular, research shows that the probability of being employed and the probability of having average earnings are both lower among military spouses relative to civilian spouses (Burke and Miller, 2017;Heaton and Krull, 2012;Hosek et al, 2002;Lim and Schulker, 2010;Lim, Golinelli, and Cho, 2007;Meadows et al, 2016). These studies generally use a combination of administrative military personnel data and survey data in which the analyses are conducted by comparing military spouses with civilian spouses while controlling for differences in demographic characteristics.…”
Section: Pcs Moves Lead To Losses In Spousal Earningsmentioning
confidence: 99%
“…Female spouses between the ages 25 and 44 had the second highest unemployment rate, at 15 percent (almost three times higher than the rate for their civilian counterparts, which was 6 percent) (Maury and Stone, 2014). Further, according to analysis of the 2014 Deployment Life Survey, female spouses who are employed earn less than comparable civilian peers in terms of raw dollars and percentage earnings; also, military wives who are part of the labor force work as many hours as their civilian counterparts but still earn significantly less for that work (Meadows, Griffin, Karney, and Pollak, 2015).…”
Section: Military Spouses' Labor Force Experiencesmentioning
confidence: 99%
“…Research has identified an hourly wage gap for military wives (Lim, Golinelli, and Cho, 2007, p. 36;Meadows, Griffin, Karney, and Pollak, 2015), who represent 92.7 percent of all spouses of active-duty personnel (U.S. Department of Defense, 2014, p. 123). Further, results from the 2013 Military Spouse Employment Survey (Maury and Stone, 2014) show differences in self-reported average gross income of wives working in a preferred versus nonpreferred career (Maury and Stone, 2014).…”
Section: Industry Typementioning
confidence: 99%